Telephone networks and transactional motherhood in Channel 4's It's A Sin. (February 2023) - Harrison, Rebecca
This article offers an analysis of women's representation in the 2021 Channel 4 series It's A Sin . Focusing on the show's narrative and ideological use of the telephone network as a system of transactional care, the article critiques depictions of motherhood and questions the erasure of narratives about experiences of gender, race, sexuality, class and disability in queer communities. By way of textual analysis and histories of communication technologies in the 1980s and 1990s, the article argues that It's A Sin perpetuates conservative and moralising perspectives on a range of issues, particularly with regard to gender and sexual activity.